Gestión administrativa y su incidencia en las ventas de la farmacia “la salud” del cantón el empalme año 2020-2021. plan de estrategias de marketing. - Loor Urban, Lisseth Viviana (2021)
This research project is oriented towards the analysis of the importance of administrative management in an organization because it constitutes a necessary tool for management that allows to properly organize and optimize activities, in the Pharmacy "La Salud" they have been detected difficulties that require further consideration, among them, the level of knowledge of the collaborators about the drugs stands out and their dosage is something that significantly affects sales, this research project aims to address a qualitative-quantitative and descriptive methodology, it tries to demonstrate by means of the historical-logical, inductive, deductive methods, allowing to analyze and interpret the data obtained through direct observation and the interview (with the pharmacy manager, accountant, employees and clients) as a collection instrument, to know the means through of which advertising is carried out, compliance of internal regulations, administrative expenses and the current commercial manual. However, the study intends to design as an alternative proposal the generation of a Marketing Strategy Plan in order to enhance or expand the operating income of the Pharmacy "La Salud" as results describe the shortcomings, problems and inconveniences raised within the processes and activities in the placement of credits will be made known to the pertinent authorities so that the preventive and corrective measures they deem appropriate are taken. Keywords: Administrative management - sales - budget - Marketing